The psychological and behavioral effects of social isolation on mass shooters - Lankford, Adam; Silva, Jason R. (Frontiers in Psychiatry, 2025)
BackgroundSocial isolation has been identified as a risk factor in the lives of mass shooters, assassins, serial killers, child molesters, lone actor terrorists, suicide attackers, and other violent offenders, but its psychological and behavioral effects are only partially understood.MethodsFor this article, we tested for bivariate differences between public mass shooters who were and were not socially isolated in the United States from 2000 to 2024.ResultsCompared to other perpetrators, socially isolated mass shooters were significantly more likely to be unemployed, single, childless, and sexually frustrated; to have a mental health problem in general, autism specifically, prior psychiatric hospitalization, and a history of suicidality (unrelated to their attack intentions); to use substances, play violent video games, adopt prejudices, seek fame, and show interest in past mass violence; and to kill more victims.DiscussionBased on these findings and other research, we propose a new model for social isolation’s effects on mass shooters’ mental health and their coping mechanisms prior to attack. We also provide illustrative case examples and offer recommendations for future research.